STUDY OF THE THERMAL EXPANSION COEFFICIENT OF SEVERAL SAND MIXTURES USED IN THE CASTING TECHNOLOGY: دراسة معامل التمدد الحراري لعدة خلائط من الرمال المستخدمة في تقنية الصب - Abbad Nofal Kassouha, Raeed Solyman Muhammad, Moustafa Hussin Aljerf (Journal of engineering sciences and information technology, 2021)
The casting technology is one of the most important production processes, because of its special characteristics and features such as the ability to produce complex shapes and a wide range of compositions. This work aims to study several mixtures of sand with different structures in terms of permeability, strength, thermal expansion coefficient, comparing them, study the effect of the elements involved in the composition of these mixtures on those parameters, and create a database that can be used both in modeling processes or mold design, as when designing the sand mold The value of the sand expansion of the mold must be taken into account, otherwise the designer will face the problem of the possibility of exit some dimensions of the final product from the permissible range and thus rejecting the product, Or the product is undergone to deformations resulting from the expansion of mold sands, which must be avoided when designing the mold Knowing the characteristics of those sand mixtures helps the investor in choosing the most appropriate mixture for the required casting process in terms of engineering specifications or quantity, with the aim of less costly production by saving in choosing the most appropriate and least expensive sand mixture that serves the desired purpose.